Problems with classification of polineuropaties severity in case of hereditary ones – review of literature - Stępień, Jakub; Pastuszak, Żanna (Journal of Education, Health and Sport, 2023)
Evaluation of neuropathy severity is still a challenge for a modern medicine. Many scales were made to resolve this problem but each of them has limitations. It is known that in case of many patients there is no relation between clinical status and nerve conduction studies (NCS) results. Severe disabled patients with neuropathies can have nerve conduction study result mild impaired and conversely relation is also often observed. Many screening instruments with numerous composite scores are used to evaluate neuropathy. Most of them involved sensory perception, motor functions and reflexes like Neuropathy Disability Score (NDS), Neuropathy Impairment Score (NIS), Thoronto Clinical Neuropathy Scoring System. Electrophysiological parameters are also useful in classification of disease types especially in Charcot-Marie-Tooth one. There were many attempts of discovering new scores especially in diabetic neuropathies, involving mainly clinical features. There is lack of easy, reliable and precise scores that could improve neuropathy classification and monitoring disease progression especially in case of hereditary polyneuropathy.